NON-STANDARD WORD WRITING IN POS KOTA NEWS TITLE - Dicky Septiawan; Nur Irwansyah; Siti Jubei (Universitas Indraprasta PGRI, 2020)
Abstract: The habit of reading the newspaper by itself will be able to familiarize readers morefamiliar with the language of the newspaper. However, in fact in terms of the users of the languagein the newspaper classified as inadequate. The public seemed never ceased to demand thenewspaper to use the language normative and standard in the presentation of news. The purpose ofthis study is to know the writing of non-standard words in the title of the Pos Kota newspaper.Furthermore, it is expected to that many readers would know about non-standard words. Theresearch method used to analyze the writing of non-standard words in the Pos Kota newspaper titleis a descriptive method. From a total of 25 words divided, Basic, Affix and Combined Words getthe same amount of 5 words. Beheading Words gets 3 words. Re-form, Prepositions s,Abbreviations and Acronyms Words get 2 words. Numbers get 1 word. Meanwhile, Particles,,Pronouns, and Article Words get 0 words. There are still a lot of non-standard vocabulary writtenin newspapers that can cause readers to be more familiar with non-standard vocabulary thanstandard vocabulary later. In the end, it will cause many errors in the use of standard vocabularyby readers.Key Words: word writing, non-standard words, Pos Kota newspaper.